Profil Kebugaran Jasmani Aspek Daya Tahan Vo2max Siswa SD Negeri 27 Bengkulu Tengah: Profile of Physical Fitness Aspects of Endurance VO2 Max of Students at SDN 27 Bengkulu Tengah - Pirsan; Tono Sugihartono; Ari Sutisyana (Universitas Bengkulu, 2023)
ABSTRACT The purpose of study was to determine the physical fitness profile of the VO2 Max endurance aspect of the students of SD Negeri 27 Bengkulu Tengah. This type of research was descriptive qualitative research. The research subjects were students in grades III, IV, V and VI of SD Negeri 27 Bengkulu Tengah. To analyze the file , the researcher used the multi fitness test (MFT)VO2 Max instrument (arrival back and forth 20 meters). The results of file analysis obtained 21 (29.16%) male students with a value score of VO2 Max <25 with a very bad category, 33 (45 ,83%) of male students with a value score of VO2 Max 25.0 - 33.7 category with a poor category, 17 (23.61%) male students with a value score of VO2 Max 33.8 - 42.5 in the medium category, 1 (1.38% )of male students with a value score of VO2 Max 42.6 was in the good category and 0 (0%) no male students in the very good category. The average V02max of male students was at a value score of VO2 Max 28.91 with a poor category. Mean while, female students found 52 (72.22% ) female students with a value score of VO2 Max <25 in the very bad category, 19 (26.38% ) female students with a value score of VO2 Max score 25.0 - 33.7 with bad category, 1(38% ) female student with a value score of VO2 Max 33.8 - 42.5 in the medium category, 0 (0%) no female students in the good category and 0 (0%) no female students in the very good category. The average V02max of female students was at a value of 24,23 with a very poor category. The average results of physical fitness aspects of endurance VO2 Max students of SD Negeri 27 Bengkulu Tengah were at a value of 26,57 with a bad category. Keywords: Physical Fitness, students of SD Negeri 27 Bengkulu Tengah, Aspects of Endurance VO2 Max